2006
DOI: 10.4049/jimmunol.177.9.6227
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV State but Not Apoptosis Depends on IFN Signature in CD4+ T Cells

Abstract: To gain insights into the molecular mechanisms underlying early host responses to HIV in the CD4+ T cell target population, we examined gene expression in CD4+ T cells isolated 24 h after ex vivo HIV infection of lymphocyte aggregate cultures derived from human tonsils. Gene profiling showed a distinct up-regulation of genes related to immune response and response to virus, notably of IFN-stimulated genes (ISGs), irrespective of the coreceptor tropism of the virus. This mostly IFN-α-dependent gene signature su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Here, we used a direct experimental approach with flow cytometry to visualize simultaneously the temporal expression patterns of cyclins A and B 1 in specific activated subsets (CD25 ϩ or HLA-DR ϩ ) of CD4 ϩ T cells and found no difference between the temporal expression patterns of cyclins A and B 1 in activated CD4 ϩ T cells from untreated, viremic HIV ϩ individuals and those of cells from HIV Ϫ individuals or of PHA-activated CD4 ϩ T cells. Our finding that activated CD4 ϩ T cells are under the influence of type I interferons in the setting of HIV-1 infection is consistent with findings of previous studies documenting type I interferon effects in CD4 ϩ T cells from the secondary lymphoid tissues of HIV ϩ individuals (5,32,35,44,53,81). However, we extend these previous studies by specifically studying the subset of activated (CD25 ϩ ) CD4 ϩ T cells from HIV ϩ T-cell response (27) but may also impart strong proliferative and survival signals to CD4 ϩ T cells (46,47).…”
Section: Cd25supporting
confidence: 82%
“…Here, we used a direct experimental approach with flow cytometry to visualize simultaneously the temporal expression patterns of cyclins A and B 1 in specific activated subsets (CD25 ϩ or HLA-DR ϩ ) of CD4 ϩ T cells and found no difference between the temporal expression patterns of cyclins A and B 1 in activated CD4 ϩ T cells from untreated, viremic HIV ϩ individuals and those of cells from HIV Ϫ individuals or of PHA-activated CD4 ϩ T cells. Our finding that activated CD4 ϩ T cells are under the influence of type I interferons in the setting of HIV-1 infection is consistent with findings of previous studies documenting type I interferon effects in CD4 ϩ T cells from the secondary lymphoid tissues of HIV ϩ individuals (5,32,35,44,53,81). However, we extend these previous studies by specifically studying the subset of activated (CD25 ϩ ) CD4 ϩ T cells from HIV ϩ T-cell response (27) but may also impart strong proliferative and survival signals to CD4 ϩ T cells (46,47).…”
Section: Cd25supporting
confidence: 82%
“…In vitro studies have shown that HIV activates pDCs to increase IFN-␣ production, which in turn upregulates the expression of TRAIL in monocytes and the expression of death receptors DR-5 on CD4 ϩ T lymphocytes (1,14,15). This mechanism is thought to be responsible for the increased susceptibility to CD4…”
Section: Vol 83 2009 T-lymphocyte Apoptosis In Siv-infected Sooty Mmentioning
confidence: 99%
“…It is unclear, however, whether IFN-α has a beneficial or harmful effect in HIV-1 infection. On the one hand, IFN-α could be beneficial, as it has been shown to directly decrease HIV-1 replication in vitro, although only partially (13). Moreover, the IFN-α effect on promoting antiviral adaptive immune responses may also result in reduced virus replication in vivo.…”
Section: Introductionmentioning
confidence: 99%